2018
DOI: 10.1002/erv.2627
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating behaviours and autistic traits—Are there any associations in nonclinical populations? A systematic review

Abstract: The existing literature indicates concurrent associations between specific autistic-like behaviours and problematic eating behaviours in nonclinical samples across ages. Large prospective longitudinal studies are needed for insight into the temporal order of these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 51 publications
5
28
0
1
Order By: Relevance
“…We scrutinized the relationship between autistic traits and eating psychopathology with a focus on one putative mediating factor that might hypothetically serve as a risk factor for ED in autistic people and those with high autistic traits: levels of alexithymia. We corroborated the relationship between autistic traits and eating psychopathology which has been previously observed with these same measures [32][33][34][35][36], but three new findings are of especial interest. These include (a) a complete or partially mediating role of alexithymia as reflected in TAS-20 scores, notably the difficulty identifying emotions aspect, in the relationship between autistic traits and eating psychopathology; (b) the influence of several other variables on this relationship, including sex, anxiety, and depression; and (c) the divergence between self-report (TAS-20) and performance-based (LEAS) measures of alexithymia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We scrutinized the relationship between autistic traits and eating psychopathology with a focus on one putative mediating factor that might hypothetically serve as a risk factor for ED in autistic people and those with high autistic traits: levels of alexithymia. We corroborated the relationship between autistic traits and eating psychopathology which has been previously observed with these same measures [32][33][34][35][36], but three new findings are of especial interest. These include (a) a complete or partially mediating role of alexithymia as reflected in TAS-20 scores, notably the difficulty identifying emotions aspect, in the relationship between autistic traits and eating psychopathology; (b) the influence of several other variables on this relationship, including sex, anxiety, and depression; and (c) the divergence between self-report (TAS-20) and performance-based (LEAS) measures of alexithymia.…”
Section: Discussionsupporting
confidence: 88%
“…Though ASC and AN are indeed dissociable, a substantial body of literature supports their common cooccurrence. In non-clinical populations, autistic traits and eating disorder symptomatology rise in tandem significantly correlated [32][33][34][35][36]. Research involving individuals with anorexia has revealed elevated autistic traits or symptomatology appear across a range of measurement tools, including screening questionnaires (such as the Autism-Spectrum Quotient (AQ) [37]) [7,[38][39][40][41][42][43][44][45], clinical interviews [46], and autism diagnostic tests [6,47], and this consistent elevation in autistic symptomatology suggests disproportionate representation of ASC in this population [5,6,48,49] 2 .…”
mentioning
confidence: 99%
“…Previous studies have also shown that higher schizophrenia PRS are associated with poorer social understanding and greater irritability, 25 domains that appear to be impaired in individuals with eating disorders 26,27 and could therefore represent intermediate phenotypes shared by these conditions. Although the majority of the literature has focused on anorexia nervosa, 28 a recent systematic review has shown that those with broader disordered eating behaviours 26 also show deficits in social cognition, and greater autistic traits. To date, these studies have been solely conducted cross-sectionally, 26 making it difficult to infer whether these cognitive deficits traits emerge before or after the onset of eating disorders.…”
Section: Comparisons With Previous Literature and Interpretation Of Tmentioning
confidence: 97%
“…These primary research publications can later be included in epidemiological systematic reviews or meta‐analyses, which are based on structuring and synthesizing the available empirical evidence in order to answer a specific research question. For example, the publication that compiles previously published results for the association of disordered eating behaviours and autistic traits in nonclinical populations (Christensen, Bentz, Clemmensen, Strandberg‐Larsen, & Olsen, 2019), or the study measuring the effectiveness of contingency management in the treatment of Anorexia nervosa patients (Ziser et al, 2018).…”
Section: Introductionmentioning
confidence: 99%